THERMAL COMFORT STUDY OF TEACHERS' ROOM AT SEKOLAH BINA MULIA PONTIANAK - Suryajaya, Albert; Caesariadi, Tri Wibowo (LANGKAU BETANG: JURNAL ARSITEKTUR, 2014)
Thermal comfort is one of the important aspects to ensure the comfort of a building. School building, e.g. Sekolah Bina Mulia, Pontianak is used for education activities for about eight hours a day. The teachersfourth floor and still applies the natural air ventilation system while other rooms use mechanical ventilation system. It is interesting to see thermal comfort condition in the ort of the room depends on the environment. Because of its position on the fourth floor, the wind circulation can flow freely and the application of air ventilation is possible. The average temperature is 29.599ºC, 71.216% for relative humidity and 0.143 m/s for wind speed, and 29.482ºC for MRT. The average value of PMV is 1.615. The thermal comfort value, based on the average of PPS*(PMV) calculation for three days observation is 0.130 and it is the neutral condition. This means the room is comfort for the users and it is mainly because  of the windows, sun shading, and the building materials which support the natural air ventilation of the school Kenyamanan termal merupakan salah satu aspek penting untuk memastikan suatu bangunan dapat memberikan kenyamanan bagi penggunanya. Bangunan sekolah, seperti Sekolah Bina Mulia Pontianak merupakan bangunan pendidikan yang digunakan kurang lebih delapan jam dalam satu hari. Ruang guru pada sekolah Bina Mulia, yang terletak pada lantai empat masih menggunakan sistem ventilasi udara alami sementara ruangan lain menggunakan sistem penghawaan mekanikal. Kenyamanan termal pada ruangan tentu sangat tergantung pada Keadaan lingkungan. Karena posisinya yang cukup tinggi, pergerakan udara pada ruangan juga lebih bebas. Artinya, aplikasi ventilasi udara alami sangat memungkinkan. Nilai temperatur udara rata-rata pada ruangan adalah 29,599 ºC, kelembaban 71,216%, kecepatan udara 0,143 m/det dan nilai temperatur radiasi 29,482ºC. Nilai PMV rata-rata pada ruangan adalah 1,615. Nilai PPS*(PMV) rata-rata pada ruangan tersebut dalam tiga hari pengamatan adalah 0,130 dan merupakan kondisi netral. Ini artinya ruangan tersebut nyaman bagi penggunanya, yang pada dasarnya dikarenakan sistem jendela, pelindung matahari, dan material bangunan dapat mendukung ventilasi udara alami pada bangunan REFERENCESAlucci, Marcia Peinando; Leonardo Marques Monteiro. 2009. Thermal Comfort Index for The Assessment of Outdoor Urban Spaces in Subtropical Climates. University of Sao Paulo. Sao PauloBrager, G.S. and R. de Dear. 2001. Climate, Comfort, & Natural Ventilation: A new adaptive comfort standard for ASHRAE Standard 55. University of California. Berkeley.Charles, Kate E. 2003. Fanger’s Thermal Comfort and Draught Models. Institute for Research in Construction. OttawaDarby, Sarah and Rebecca White. 2005. Thermal Comfort. University of Oxford. LondonHensen, J.L.M. 1990. Literature Review on Thermal Comfort in Tranisent Conditions. Eindhoven University of Technology. EindhovenMangunwijaya, Yusuf Bilyarta. 1929. Pengantar Fisika Bangunan. Djambatan. JakartaMors, Sanderter, Jan L. M. Hensen, Marcel Loomans, Atze Boerstra. 2011. Adaptive thermal comfort in primary school classrooms: Creating and validating PMV-based comfort charts. Eindhoven University of Technology. EindhovenOrosa, Jose A. 2009. Research on the Origins of Thermal Comfort. University of A Coruña. A CoruñaParsons, Ken. 2003. Human Thermal Environments: The effect of Hot, Modern, and Cold Environments on Human Health, Comfort, and Performance. Tj International Ltd. CornwallPau, J.S., William K.S. Pao, Shaharin A. Sulaiman, and E. Halawa. 2013. Adaptive Thermal’s Model for Optimum Thermal Comfort Setting fo Lecture Halls in Malaysia. CREAM - Current Research in Malaysia Vol.2, No. 2Satwiko, Prasasto. 2005. Fisika Bangunan 1 Edisi 2. Andi. Yogyakarta